Proyecto de inversión para la creación de una empresa productora de licor anisado en la parroquia Malacatos y su comercialización en la provincia de Loja - Ocampo Cuenca, Adela María (2015)
To make the "INVESTMENT PROJECT FOR THE CREATION OF A producer of aniseed liquor IN Malacatos PARISH AND MARKETING IN THE PROVINCE OF LOJA" was necessary to develop according to the general objective and specific objectives it will serve to qualify for the Commercial Engineering degree. The first objective is to study market succeeded in determining that the potential demand is 144497 Year 1 and Year 5 161 373, the actual demand is the first year of 112707 and 125871 last year and effective 112707 Year 1 and Year 5 125 871; whose per capita consumption was 32.95, giving a total effective demand for 89,129,008 and 99,538,585 respectively; as well as offering the first year was five 3782335 and 3970318; existing demonstrating that there is an unmet demand for 85346673 and 95568267 for the years 1 and 5 so the project has acceptance in the local market. The second objective is to conduct a technical study established that the company will be located in the parish of Malacatos for ease of raw materials, skilled labor and determining the installed capacity of the project 124800 with a participation rate of 80% to It corresponds to a capacity utilization 99840; project engineering also indicated; thereby disclosed where the business work, processes, machinery and equipment required for normal operation. The third objective is to make the legal and administrative organization are shown in graphical form the organizational structure and the different functions and activities that each employee must perform to a proper development of the company and it is given to know the legal formalities necessary for the Consitución thereof. The fourth goal made it through the economic-financial study, so that the initial investment project which amounted to $ 111,849.97, budget revenues $ 396,433.28 and $ 448,418.23 was defined; with expenditures of $ 264,288.85 and $ 298,945.48 in years 1 and 5 respectively, the difference of cash inflows and outflows gave as result of cash flows $ 89,126.40 and $ 105,881.13; financial indicators such as net present value was $ 189,108.15, Internal Rate of Return is 77.55%, 1.50 Benefit Cost Ratio, Capital Recovery Period 6months 1 year and 18 days and Sensitivity Analysis with increase in cost and declining revenue was 0.99 which shows the feasibility of the project. Finally we conclude that this investment project is feasible, since each of the studies conducted gave favorable results for the investor which is considered appropriate implementation based on each of the techniques which will help the company remain and grow on the market